Endometriosis: seeking optimal management in women approaching menopause. (4th July 2019) - Alio, L.; Angioni, S.; Arena, S.; Bartiromo, L.; Bergamini, V.; Berlanda, N.; Bonanni, V.; Bonin, C.; Buggio, L.; Candiani, M.; Centini, G.; D'Alterio, M. N.; et al.
Abstract: The incidence of endometriosis in middle-aged women is not minimal compared to that in the reproductive age group. The treatment of affected women after childbearing age to the natural transition toward menopause has received considerably poor attention. Disease management is problematic for these women due to increased contraindications regarding hormonal treatment and the possibility for malignant transformation, considering the increased cancer risk in patients with a long-standing history of the disease. This state-of-the-art review aims for the first time to assess the benefits of the available therapies to help guide treatment decisions for the care of endometriosis in women approaching menopause. Progestins are proven effective in reducing pain and should be preferred in these women. According to the international guidelines that lack precise recommendations, hysterectomy with bilateral salpingo-oophorectomy should be the definitive therapy in women who have completed their reproductive arc, if medical therapy has failed. Strict surveillance or surgery with removal of affected gonads should be considered in cases of long-standing or recurrent endometriomas, especially in the presence of modifications of ultrasonographic cyst patterns. Although rare, malignant transformation of various tissues in endometriosis patients has been described, and management is herein discussed.